Peran Pedoman Safety Management System pada Perguruan Tinggi Dalam Negeri dalam Menghadapi Ancaman Pandemi Virus - Taufiqur Rachman; Arief Suwandi; Nofi Erni; M. Derajat Amperajaya; Rina Anindita (Universitas Teuku Umar, 2022)
The COVID-19 pandemic has changed the shape of the world of work. This change makes 100% of universities in Indonesia conduct online learning, but some academic administrative activities are still carried out on campus. With this condition, higher education management faces two things that must be considered, namely the health of employees who are still working on campus, and teaching staff who work at home. The purpose of this study is to make the right size in measuring the Safety Management System in Higher Education in dealing with the threat of the virus and to examine the role of Management Commitment to the implementation of the Safety Management System and to examine the role of Safety Culture in the implementation of the Safety Management System. This research is a survey research using a questionnaire, with data analysis method using Path Analysis and Binomial Regression and validity test using Confirmatory Factor Analysis. From the results of this study, it can be seen that a high Safety Culture cannot improve Safety Performance in Higher Education during the pandemic, which is different from Management Commitment and the Safety Management System which are the main determinants of employee Safety Performance during the pandemic. Management's commitment can indeed improve employee Safety Performance during a pandemic, but in improving Safety Performance during a pandemic, performance will be higher if the management commitment pushes the Safety Management System first, then it will increase the organization's Safety Performance with the virus pandemic.